Fundamentals of entrepreneurship (ENT300) : Muslimah fashionista boutique / Siti Nursuriani Abdullah Rambli ... [et al.] - Abdullah Rambli, Siti Nursuriani; Hamali, Nur Aziah Jasmin; Awang Omar, Noor Masmarini; Su'ut, Lily Suriani; Nasir, Norjas (2016)
After doing extensive research on the business opportunity available in Kota Samarahan, we are choosing Summer Mall, Kota Samarahan as our main target market. The reasons why we choose that area because Summer Mall is a strategic place which everyone staying or studying in Kota Samarahan be familiar with the area. In this case, we would like to start our business which focus on Muslimah wear. We provided differences and up-to-date styles and designs that customers will have attraction on it.In this process of establishing the business plan, all aspects including the four major of business establishment such as Marketing, Operational, Administration and Financial are seriously taken into consideration